Brain metastases as the first clinical manifestation of prostate cancer: a case report - Nikolai A. Ognerubov; Ruslan S. Sergeev; Dmitriy M. Mikhalev (Consilium Medicum, 2023)
Background. Intracranial metastases, as the first clinical symptom of prostate cancer (PC), are extremely rare, with only anecdotal case reports in the literature.